Effect of reducing medication regimen complexity on glycaemic control in patients with diabetes - Abdelaziz Tarek Samy; Sadek Khaled Marzouk (Sciendo, 2019)
Introduction. Medication Regimen complexity is an important issue of patients care that needs to be addressed. The aim of this study is the safe reduction of regimens complexities. The effect of this intervention on glycemic control was assessed in this study.